Combining Attractants and Larvicides in Biodegradable Matrices for Sustainable Mosquito Vector Control. - Dirk Louis P Schorkopf; Christos G Spanoudis; Leonard E G Mboera; Agenor Mafra-Neto; Rickard Ignell; Teun Dekker (Public Library of Science (PLoS), 2016)
BACKGROUND:There is a global need for cost-effective and environmentally friendly tools for control of mosquitoes and mosquito-borne diseases. One potential way to achieve this is to combine already available tools to gain synergistic effects to reduce vector mosquito populations. Another possible way to improve mosquito control is to extend the active period of a given control agent, enabling less frequent applications and consequently, more efficient and longer lasting vector population suppression. METHODOLOGY/PRINCIPAL FINDINGS:We investigated the potential of biodegradable wax emulsions to improve the performance of semiochemical attractants for gravid female culicine vectors of disease, as well as to achieve more effective control of their aquatic larval offspring. As an attractant for gravid females, we selected acetoxy hexadecanolide (AHD), the Culex oviposition pheromone. As toxicant for mosquito larvae, we chose the biological larvicides Bacillus thuringiensis israelensis (Bti) and Bacillus sphaericus (Bs). These attractant and larvicidal agents were incorporated, separately and in combination, into a biodegradable wax emulsion, a commercially available product called SPLAT (Specialized Pheromone & Lure Application Technology) and SPLATbac, which contains 8.33% Bti and 8.33% Bs. Wax emulsions were applied to water surfaces as buoyant pellets of 20 mg each. Dose-mortality analyses of Culex quinquefasciatus Say larvae demonstrated that a single 20 mg pellet of a 10-1 dilution of SPLATbac in a larval tray containing 1 L of water caused 100% mortality of neonate (1st instar) larvae for at least five weeks after application. Mortality of 3rd instar larvae remained equally high with SPLATbac dilutions down to 10-2 for over two weeks post application. Subsequently, AHD was added to SPLAT (emulsion only, without Bs or Bti) to attract gravid females (SPLATahd), or together with biological larvicides to attract ovipositing females and kill emerging larvae (SPLATbacAHD, 10-1 dilution) in both laboratory and semi-field settings. The formulations containing AHD, irrespective of presence of larvicides, were strongly preferred as an oviposition substrate by gravid female mosquitoes over controls for more than two weeks post application. Experiments conducted under semi-field settings (large screened greenhouse, emulating field conditions) confirmed the results obtained in the laboratory. The combination of attractant and larvicidal agents in a single formulation resulted in a substantial increase in larval mosquito mortality when compared to formulations containing the larvicide agents alone. CONCLUSIONS/SIGNIFICANCE:Collectively, our data demonstrate the potential for the effective use of wax emulsions as slow release matrices for mosquito attractants and control agents. The results indicate that the combination of an oviposition attractant with larvicides could synergize the control of mosquito disease vectors, specifically Cx. quinquefasciatus, a nuisance pest and circumtropical vector of lymphatic filariasis and encephalitis.